Dynamic power management modelling of a wireless sensor node. Issue 2 (22nd June 2022) - Kallimani, Rakhee; Iyer, Sridhar
Currently there is a growing attention to design low power and energy-efficient nodes for wireless sensor networks. The critical issue which captures the attention of the researchers is the energy constraint and the lifetime of individual nodes of the network. Among the many power management techniques, Dynamic Power Management (DPM) is the most promising technique to control and save the usage of energy of the node and enhance the lifetime. The article proposes an analyser based event driven sensor node modelled using SimEvents. The model demonstrates the stochastic behaviour of an input event arrival with First In First Out Queue, and a single server. The article employs semi-Markov based DPM to analyse the power behaviour of the sensor node. The developed model is analysed for the power consumption and the lifetime as the performance metrics. The results prove that factors such as arrival rate and change detection probability affect the lifetime and power consumption of an individual node. It is observed that maximum of 237 mW of power is consumed by the node for 85 events/hour and is lasts for 78 days. Further, the effect of event arrival and the change detection probability on the model is also analysed.